Changing prevalence of wheeze, rhinitis and allergic sensitisation in late childhood: findings from 2 Isle of Wight birth cohorts 12 years apart. Issue 9 (September 2015) - Patil, V. K.; Kurukulaaratchy, R. J.; Venter, C.; Grundy, J.; Roberts, G.; Dean, T.; Arshad, S. H.
Summary Background While the prevalence of asthma in children is decreasing or remaining the same, time trends in the prevalence of rhinitis in children are not known. Understanding sensitisation trends may help inform about trends in asthma and rhinitis prevalence. Objective To assess time trends of wheeze, rhinitis and aero‐allergen sensitisation prevalence at 10 years of age, we compared two birth cohorts established 12 years apart. To gain insight into differences in disease prevalence, we assessed association of family history, early life exposures and sensitisation with wheeze and rhinitis in each cohort. Methods The IoW (Isle of Wight) and FAIR (Food Allergy and Intolerance Research) unselected birth cohorts were established in 1989 and 2001 respectively in IoW. Identical ISAAC questionnaire and skin prick test data were collected and compared at 10 years of age. Results Over the 12‐year period from 2001 to 2012, prevalence of lifetime wheeze, current wheeze and those ever treated for asthma decreased by 15.9% (45.5 vs. 29.6, P < 0.001), 3.9% (18.9 vs. 15, P = 0.020) and 8.2% (31.7 vs. 23.5, P = 0.001), respectively. Conversely, current rhinitis and lifetime rhinitis prevalence increased by 5.5% (22.6 vs. 28.1, P = 0.004) and 13% (18.6 vs. 31.7, P < 0.001), respectively. Atopic status remained stable; however, house dust mite (HDM) sensitisation decreased by 5.6% (19.2 vs. 13.6, P = 0.004) and grass sensitisation increased by 3.5% (12.9 vs. 16.4, P = 0.054). Male sex, parental history of asthma and HDM sensitisation were significantly associated with lifetime wheeze in both cohorts, while maternal smoking during pregnancy was a significant risk factor only in the earlier IoW cohort. Parental history of rhinitis and grass sensitisation was significantly associated with lifetime rhinitis in both cohorts, while HDM sensitisation was significant only for the IoW cohort. Conclusion Contrasting changes were noted with falling wheeze and HDM sensitisation but rising rhinitis and grass sensitisation prevalence. Changing prevalence of aero‐allergen sensitisations may explain the different time trends observed in these cohorts.